Burden of breast cancer and attributable risk factors in the North Africa and Middle East region, 1990–2019: a systematic analysis for the Global Burden of Disease Study 2019 - Azadnajafabad, Sina; Saeedi Moghaddam, Sahar; Mohammadi, Esmaeil; Rezaei, Negar; Rashidi, Mohammad-Mahdi; Rezaei, Nazila; Mokdad, Ali H.; Naghavi, Mohsen; Murray, Christopher J. L.; Larijani, Bagher; Farzadfar, Farshad; , GBD 2019 NAME Breast Cancer Collaborators; et al. (Frontiers in Oncology, 2023)
Background: Breast cancer (BC) is the most common cancer of women globally. The North Africa and Middle East (NAME) region is coping hard with the burden of BC. We aimed to present the latest epidemiology of BC and its risk factors in this region. Methods: We retrieved the data on BC burden and risk factors from the Global Burden of Disease Study 2019 to describe BC status in the 21 countries of the NAME region from 1990 to 2019. We explored BC incidence, prevalence, deaths, disability-adjusted life years (DALYs), and attributable burden to seven risk factors of female BC including alcohol use, diet high in red meat, low physical activity, smoking, secondhand smoke, high body-mass index and high fasting plasma glucose. Decomposition analysis on BC incidence trend was done to find out the contributing factors to this cancer’s growth. Results: In 2019, there were 835 576 (95% Uncertainty Interval: 741 968 to 944 851) female and 10 938 (9030 to 13 256) male prevalent cases of BC in the NAME region. This number lead to 35 405 (30 676 to 40 571) deaths among females and 809 (654 to 1002) deaths in males in this year. BC was responsible for 1 222 835 (1 053 073 to 1 411 009) DALYs among females in 2019, with a greater proportion (94.9%) of burden in years of life lost (YLLs). The major contributor to female BC incidence increase in the past three decades was found to be increase in age-specific incidence rates of BC (227.5%), compared to population growth (73.8%) and aging (81.8%). The behavioral risk factors were responsible for majority of attributable female BC burden (DALYs: 106 026 [66 614 to 144 247]). High fasting plasma glucose was found to be the risk factor with largest effect (DALYs: 84 912 [17 377 to 192 838]) on female BC burden. Conclusions: The increasing incidence and burden of BC in NAME region is remarkable, especially when considering limited resources in the developing countries of this region. Proper policies like expanding screening programs and careful resource management are needed to effectively handle BC burden.